2021
DOI: 10.3389/fonc.2020.582239
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR-423-5p Contributes to the Radioresistance in Colorectal Cancer Cells

Abstract: Resistance to radiotherapy is the main reason causing treatment failure in locally advanced rectal cancer. MicroRNAs (miRNAs) have been well demonstrated to regulate cancer development and progression. However, how miRNAs regulate radiotherapy resistance in colorectal cancer remains unknown. Herein, we established two human colorectal cancer cell lines resistant to radiotherapy, named HCT116-R and RKO-R, using the strategy of fractionated irradiation. The radioresistant phenotypical changes of the two cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…In this study, we tried to determine the upstream miRNAs of LIMK2 based on the ceRNA hypothesis; with the help of the miMAP, miRDB, StarBASE, and TargetScan databases, we found that miR-423-5p is likely to be the upstream regulatory miRNA of the LIMK2 gene in LUSC. Studies have demonstrated that miR-423-5p is associated with tumor development and poor prognosis of patients (43)(44)(45)(46)(47). Then, upstream regulatory lncRNAs of miR-423-5p/LIMK2 were predicted by the StarBASE and lncBASE databases.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we tried to determine the upstream miRNAs of LIMK2 based on the ceRNA hypothesis; with the help of the miMAP, miRDB, StarBASE, and TargetScan databases, we found that miR-423-5p is likely to be the upstream regulatory miRNA of the LIMK2 gene in LUSC. Studies have demonstrated that miR-423-5p is associated with tumor development and poor prognosis of patients (43)(44)(45)(46)(47). Then, upstream regulatory lncRNAs of miR-423-5p/LIMK2 were predicted by the StarBASE and lncBASE databases.…”
Section: Discussionmentioning
confidence: 99%
“…Several miRNAs involved in cancer show dysregulated expression in ASD LCLs, including miR-6732-3p , hsa-miR-221-5p [ 64 , 65 ], hsa-miR-21-5p [ 66 , 67 ], hsa-miR-152-3p [ 68 , 69 ], hsa-miR-3529-3p [ 70 , 71 ], and has-miR-148b-3p [ 72 , 73 ]. Additionally, miR-3529-3p was 2-fold upregulated in ASD LCLs and it targets GABRA4 ( Table S7 ) and this miRNA promotes angiogenesis [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, miR-3529-3p was 2-fold upregulated in ASD LCLs and it targets GABRA4 ( Table S7 ) and this miRNA promotes angiogenesis [ 71 ]. Studies have shown miR-3529-3p to be upregulated in radiotherapy-resistant colorectal cancer cells [ 70 ] and downregulated in liver cancer [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-3529-3p overexpression also negatively impacts OS. miR-3529-3p is upregulated in radiotherapy-resistant colorectal cancer cells [ 76 ]. To our best knowledge, this is the first study to demonstrate an association between miR-3529-3p and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%